2016
DOI: 10.1016/j.syapm.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium anhuiense as the predominant microsymbionts of Lathyrus maritimus along the Shandong Peninsula seashore line

Abstract: a b s t r a c tBeach pea [Lathyrus maritimus Bigelow, or Lathyrus japonicus subsp. maritimus (L.) P.W. Ball] is a wild legume distributed on the seashore line, and the rhizobia nodulating with this plant have been reported only rarely. In order to reveal the diversity of beach pea rhizobia on the seashore line of Shandong Peninsula, China, a total of 124 bacterial strains were isolated from the root nodules of beach pea plants collected from five sites. All the isolates were divided into five recA types after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
4
0
3
Order By: Relevance
“…In the present study, the failure to amplify both nodC and nifH from B. huanghuaihaiense 65,027 and 65,047 is consistent with their failure in nodulation; thus, they might be nonsymbiotic endophytes for peanut, similar to the other nonsymbiotic bacteria isolated from Lathyrus maritimus, Caragana jubata and Oxytropis ochrocephala [21,46]. However, the reason for the failure of amplification of nodC from B. guangdongense 61,102, B. yuanmingense 65,010, Bradyrhizobium sp.…”
Section: Symbiotic Genes and Nodulation Testsupporting
confidence: 71%
See 1 more Smart Citation
“…In the present study, the failure to amplify both nodC and nifH from B. huanghuaihaiense 65,027 and 65,047 is consistent with their failure in nodulation; thus, they might be nonsymbiotic endophytes for peanut, similar to the other nonsymbiotic bacteria isolated from Lathyrus maritimus, Caragana jubata and Oxytropis ochrocephala [21,46]. However, the reason for the failure of amplification of nodC from B. guangdongense 61,102, B. yuanmingense 65,010, Bradyrhizobium sp.…”
Section: Symbiotic Genes and Nodulation Testsupporting
confidence: 71%
“…All the recA sequences obtained in this study were aligned using Clustal W software [48], and then the haplotype was determined using DNASP v5 [25]. Since recA sequence analysis has been used as an effective marker to select representative strains of both slow-and fast-growing rhizobia [20,21,48], a representative sequence and the corresponding isolate for each recA haplotype were randomly selected for further study.…”
Section: Pcr Amplification Of Housekeeping Igs and Symbiotic Genesmentioning
confidence: 99%
“…Thus, recA is superior to other markers and could be widely used in defining rhizobial haplotypes. The definition of 41 haplotypes in Bradyrhizobium based on recA sequences among these isolates primitively evidenced their great genetic diversity and further confirmed the recA sequence analysis as an effective screening method to group the rhizobial isolates, identify the genus, and select the representative strains ( Supplementary Tables 1 , 2 ) for further phylogenetic study ( Li et al, 2016a , b ; Shao et al, 2020 ; Zhang et al, 2020 ). In MLSA of the five housekeeping genes ( glnII , dnaK , gyrB , rpoB , and recA ), the identification of 18 Bradyrhizobium genospecies among the isolates revealed that V. minima only nodulated with Bradyrhizobium in the studied sites that is consistent with the cultured Vigna species ( Yang et al, 2008 ; Han et al, 2009 ; Hakim et al, 2018 ; Ibny et al, 2019 ).…”
Section: Discussionmentioning
confidence: 58%
“…Multilocus sequence analysis (MLSA) was conducted by combining the sequences of five housekeeping genes ( dnaK , glnII , gyrB , recA , and rpoB ), and the sequence similarities between representative and reference strains were calculated using MEGA 7.0 ( Kumar et al, 2016 ). A threshold of 97% sequence similarity was used to define genospecies as suggested previously ( Cao et al, 2014 ; Li et al, 2016b ).…”
Section: Methodsmentioning
confidence: 99%
“…9 99,9 99,9 99,9 99,9 98,3 98,9 98,9 98 9 96,9 88,9 87,9 87,9 87,9 P. endophyticum [25]. Бактерии R. anhuiense являются также микросимбионтами чины японской Lathyrus japonicus [26]. Было показано, что для L. japonicus ха-рактерна очень высокая способность к азотфиксации, особенно в условиях низких температур арктического и субарктического регионов, где данное растение рассматривается в качестве перспективной кормовой культуры [27].…”
Section: экологическая генетикаunclassified